2011
DOI: 10.1302/0301-620x.93b4.25707
|View full text |Cite
|
Sign up to set email alerts
|

The role of patient factors and implant position in squeaking of ceramic-on-ceramic total hip replacements

Abstract: We investigated factors that were thought to be associated with an increased incidence of squeaking of ceramic-on-ceramic total hip replacements. Between June 1997 and December 2008 the three senior authors implanted 2406 primary total hip replacements with a ceramic-on-ceramic bearing surface. The mean follow-up was 10.6 years. The diagnosis was primary osteoarthritis in each case, and no patient had undergone previous surgery to the hip. We identified 74 squeaking hips (73 patients) giving an incidence of 3.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
88
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(93 citation statements)
references
References 19 publications
2
88
0
3
Order By: Relevance
“…Heavier and more active patients have an increased risk of squeaking due to increased mechanical loading. 38 Component orientations associated with impingement or edge loading have been associated with squeaking, thus highlighting again the importance of cup positioning. 38 It follows that an implant design that increases the risk of impingement or edge loading should be associated with higher than normal rates of squeaking, and indeed this has been reported for the Trident device.…”
Section: Impulse Generationmentioning
confidence: 99%
See 1 more Smart Citation
“…Heavier and more active patients have an increased risk of squeaking due to increased mechanical loading. 38 Component orientations associated with impingement or edge loading have been associated with squeaking, thus highlighting again the importance of cup positioning. 38 It follows that an implant design that increases the risk of impingement or edge loading should be associated with higher than normal rates of squeaking, and indeed this has been reported for the Trident device.…”
Section: Impulse Generationmentioning
confidence: 99%
“…38 Component orientations associated with impingement or edge loading have been associated with squeaking, thus highlighting again the importance of cup positioning. 38 It follows that an implant design that increases the risk of impingement or edge loading should be associated with higher than normal rates of squeaking, and indeed this has been reported for the Trident device. 39 The elevated titanium rim of this device (see Figure 2) reduces the available range of motion, thus increasing the risk of neck to rim impingement and subsequent edge loading.…”
Section: Impulse Generationmentioning
confidence: 99%
“…Some authors reported that squeaky hips are associated with younger active, heavier, and taller patients [36][37] . Parvizi et al revealed an association with a particular prosthetic design that enabled neck impingement on the metallic rim of the cup 38,39 .…”
Section: Squeakingmentioning
confidence: 99%
“…The advent and popularity of alternative bearing surfaces has been accompanied by new complications such as polyethylene liner fracture, acoustic phenomenon, metal sensitivity, and pseudotumors. Acetabular component position has been implicated as one of several causative factors for each of these complications [21][22][23][24][25] . Higher wear rates in both conventional 26 and hard-on-hard 27 bearings are seen with higher abduction angles.…”
mentioning
confidence: 99%